Holistic Integration in the Processing of Chinese Characters as Revealed by Electroencephalography Frequency Tagging. (June 2020) - Cai, Yazhi; Mao, Yudi; Ku, Yixuan; Chen, Jing
It is debated whether perceptual expertise of nonface objects, such as visual words, is indicated by holistic processing, which is regarded as a marker of perceptual expertise of faces. We address this question by frequency-tagged electroencephalography. Different parts of real or pseudo Chinese characters are presented at distinctive frequencies (6 or 7.2 Hz), which induce frequency-tagged steady-state visual-evoked potentials at occipital brain areas. The intermodulation response (e.g., 6 + 7.2 = 13.2 Hz) would emerge when holistic integration takes place. Our results suggest that the intermodulation response to the real characters is left lateralized, which is contralateral to previous findings with faces. Furthermore, at the left occipital area, the intermodulation response to real characters is more prominent than pseudo characters, suggesting that holistic integration is enhanced for real characters than for pseudo ones. Taken together, our findings suggest that holistic integration is potentially a general expertise marker for both faces and non-face objects.